液力机械式自动变速器换挡过程最优控制仿真研究 - 祝胜; 吴光强 (Jixie chuandong)
The shift control is one of the key areas in automatic transmission control.The characteristic of shifting process of an automatic transmission is discussed and the state space equation with disturbance is established according to shifting process simplified model.Based on the linear quadratic optimal control theory,the simulation and study of the clutch torque control during shifting is carried out,with slip loss and jerk considered in the target function.The study result shows that the shifting process with optimal control applied presents good shift quality in different operating conduction.The jerk and slip loss during shifting are influenced by the input torque and the load resistance,among which the input toque has a greater contribution.Meanwhile,in system design aspect,the shift quality is also affected by equivalent rotary inertia of the turbine end and the vehicle mass.